FRAYLE DELGADO, LUIS, La lucha de Jacob. - Gordo, Gemma (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Claves de la agonía de Unamuno (Editorial San Esteban, Salamanca, 2006), 167 pp.